Application of Eco-enzymes from Nutmeg, Clove, and Eucalyptus Plant Waste in Inhibiting the Growth of E. coli and S. aureus In Vitro - Rijal, Muhammad (Biosel Biology Science and Education, 2022)
Eco-enzyme is a liquid produced from the fermentation of non-fat organic matter as an environmentally friendly antiseptic with no harmful residues to the environment. Organic materials commonly used in the manufacture of eco-enzymes include vegetables and fruit wastes. Therefore, this study aims to produce eco-enzymes from organic wastes in the form of nutmeg, clove, and eucalyptus leaves. A laboratory experiment with a post-test-only control group design was carried out for 7 months from March to September 2021. The variable X includes the type of plant waste from which the eco-enzyme was obtained namely nutmeg flesh (BP), nutmeg leaf (DP), eucalyptus leaf (DK), clove leaf (DC), liquid antiseptic (Ae), and gel antiseptic (Ai), while variable Y was the level of E. coli and S. aureus (mm) growth inhibition. The results showed that different plant wastes' eco-enzymes also had distinctive colors, where DP and DK were brown, BP was reddish-brown, while DC appeared blackish-brown and clear. These differences occur due to variations in the chemical composition of each material used. Furthermore, the acidic aroma from each eco-enzyme was derived from the decomposition of alcohol compounds into acetic acid during aerobic respiration. The aroma was distinctively different depending on the type of plant waste used. Eco-enzymes and commercial antiseptics also have different abilities to inhibit E. coli and S. aureus growth with the highest inhibition found in eco-enzymes made from eucalyptus leaf waste. Keywords: Antiseptic, Cloves, Nutmeg, Eucalyptus